Improving the efficacy of plant-made anti-HIV monoclonal antibodies for clinical use - Grandits, Melanie; Grünwald-Gruber, Clemens; Gastine, Silke; Standing, Joseph F.; Reljic, Rajko; Teh, Audrey Y-H.; Ma, Julian K-C. (Frontiers in Plant Science, 2023)
Broadly neutralising antibodies are promising candidates for preventing and treating Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS), as an alternative to or in combination with antiretroviral therapy (ART). These bind to sites on the virus essential for virus attachment and entry, thereby inhibiting entry into the host cell. However, the cost of monoclonal antibodies, especially combinations of antibodies, hampers implementation of anti-HIV bNAb therapies in low- to middle- income countries (LMICs) where HIV-1 prevalence is highest We have produced three HIV broadly neutralizing antibodies (bNAbs), 10-1074, VRC01 and 3BNC117 in the Nicotiana benthamiana transient expression system. The impact of specific modifications to enhance potency and efficacy were assessed. To prolong half-life and increase bioavailability, a M252Y/S254T/T256E (YTE) or M428L/N434S (LS) mutation was introduced. To increase antibody dependent cellular cytotoxicity (ADCC), we expressed an afucosylated version of the CH2 glycan using a glycoengineered plant line. The majority of bNAbs and their variants could be expressed at acceptable yields of up to 47 mg/kg. Neither the expression system nor the modifications impacted the neutralization potential of the bNAbs. Afucosylated bNAbs exhibit enhanced ability to bind to FcγRIIIa and trigger ADCC, regardless of the presence of Fc amino acid mutations. Lastly, we demonstrated that Fc-modified variants expressed in plants show enhanced pointing to FcRn, which results in a favourable in vivo pharmacokinetic profile compared to their unmodified counterparts.